(untitled) (Bangladesh Medical Journal, 2016)
Stroke represents a continuously evolving medical and social problem, being the third leading cause of death after heart disease and cancer in developed countries. Acute kidney injury (AKI) may develop as a possible complication after acute stroke. Insufficient care of acute stroke patients is an important factor behind it. It may be associated with a significant burden of morbidity and mortality. This cross sectional observational study was conducted in Mymensingh Medical College & Hospital, Mymensingh from July 2012 to June 2014. A total of 240 patients with newly detected acute stroke confirmed by CT scan of brain were included in this study. According to this study, 15.42% of acute stroke patients developed AKI. Majority (54.05%) of the AKI patients were in >60 years age group. 17.93 % of male patients developed AKI and 11.58% of female patients developed AKI. So, AKI was a common complication after acute stroke. Early diagnosis and management of AKI may be an important part of management of these stroke patients. Bangladesh Med J. 2015 May; 44 (2): 82-86